Realização de valores pessoais no ambiente organizacional como componente de compatibilidade indivíduo-organização percebida e sua influência em intenção de saída - Santos, Leonardo Blanco dos (2016)
Voluntary exit occurs when professionals decide to leave the organisation in which they work. It generates costs not only for the organisation but also for themselves. A number of variables influence the exit, being intention to leave its strongest predictor. Based on interactional psychology, studies on person-organisation fit postulate that behaviour is a function of the interaction between characteristics of the individual and of the organisational environment. Intention to leave is one of the most researched variables in person-organisation fit. Considering the importance of values for studies on person-organisation fit, this study states the Realisation of Personal Values in the organisational environment, concept that was introduced by Maurino and Domenico (2012), as a component of perceived person-organisation fit. This study aims to verify whether the perception of Realisation of Personal Values in the organisational environment, proposed as a component of perceived person-organisation fit, influences upon intention to leave the organisation. It looks at the influence of Realisation of Personal Values in the organisational environment on intention to leave that environment. The research instrument consisted of questionnaires to measure personal values, Realisation of Personal Values in the organisational environment, intention to leave, as well as sociodemographic and functional questions. This was applied online, obtaining responses of 553 participants who worked within organisations in Brazil. The data were analyzed by statistical techniques such as analysis of variance (ANOVA), confirmatory (for personal values and Realisation of Personal Values) and exploratory (for intention to leave) factor analysis, correlations, structural equation modeling and cluster analysis. The main finding was that respondents’ perceptions of their realisation of Openess to change and Self-Enhancement values in the organisational environment influence their intention to leave. It was observed that three control variables, namely having dependents, managerial/nonmanagerial position and educational level influence on intention to leave as well. The results of cluster analysis suggest that the greater the distance between the importance attributed to a particular value and the perception of its realisation in the organisational environment, the higher is the level of intention to leave. This study contributes to the literature on perceived person-organisation fit by identifying one of its components, Realisation of Personal Values (RPV), thereby integrating RPV with the studies of person-organisation fit. A new questionnaire was developed to measure RPV based on the refined theory of personal values (SCHWARTZ et al., 2012), and by investigating the influence of RPV on intention to leave. It contributes to the organisations by inserting the possibility of considering the role of RPV on staff turnover management.